ln(13)-ln(2x)=ln(52)

Simple and best practice solution for ln(13)-ln(2x)=ln(52) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(13)-ln(2x)=ln(52) equation:


Simplifying
ln(13) + -1ln(2x) = ln(52)

Reorder the terms for easier multiplication:
13ln + -1ln(2x) = ln(52)

Remove parenthesis around (2x)
13ln + -1ln * 2x = ln(52)

Reorder the terms for easier multiplication:
13ln + -1 * 2ln * x = ln(52)

Multiply -1 * 2
13ln + -2ln * x = ln(52)

Multiply ln * x
13ln + -2lnx = ln(52)

Reorder the terms for easier multiplication:
13ln + -2lnx = 52ln

Solving
13ln + -2lnx = 52ln

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-52ln' to each side of the equation.
13ln + -52ln + -2lnx = 52ln + -52ln

Combine like terms: 13ln + -52ln = -39ln
-39ln + -2lnx = 52ln + -52ln

Combine like terms: 52ln + -52ln = 0
-39ln + -2lnx = 0

Factor out the Greatest Common Factor (GCF), '-1ln'.
-1ln(39 + 2x) = 0

Ignore the factor -1.

Subproblem 1

Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(39 + 2x)' equal to zero and attempt to solve: Simplifying 39 + 2x = 0 Solving 39 + 2x = 0 Move all terms containing l to the left, all other terms to the right. Add '-39' to each side of the equation. 39 + -39 + 2x = 0 + -39 Combine like terms: 39 + -39 = 0 0 + 2x = 0 + -39 2x = 0 + -39 Combine like terms: 0 + -39 = -39 2x = -39 Add '-2x' to each side of the equation. 2x + -2x = -39 + -2x Combine like terms: 2x + -2x = 0 0 = -39 + -2x Simplifying 0 = -39 + -2x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 3x^2-4=4x | | 8+8q=9+7q | | m^2+6m-91= | | -5=x/2-5 | | -8c+5=-2-4c | | 38-6b=4(4b+4) | | x+.80(2)=.90(x+2) | | 5x^2y^3(2xy^3+3x^4y)= | | 8-10x=84-38x | | x+47=7x-13 | | x^2-3x+4=5 | | -2-7p=1-7p | | -12+5k=2k+3 | | 2x-3=-2x+5 | | 9x-22=6x+11 | | -2(1+7x)=-8x-32 | | n/5=-12 | | 9x(x+9)= | | y/3=8 | | 2t-3+8=3t-8 | | x/4=-12 | | x^2-11x=(-28) | | 3-f=6f+24 | | 13-2x=7x+5 | | -7(3v+6)=-7v+28 | | -x-6=-x^2 | | -9w=54 | | -b=-6 | | -8a=64 | | -39+7n=8(2n+3) | | 3(t-6)+5t=4(2t+3)-11 | | -4x+9=3x-12 |

Equations solver categories